Religious Identifications in Late Antique Papyri : 3rd--12th Century Egypt. - Brand, Mattias. (Taylor & Francis Group, 2022)
This volume provides novel social-scientific and historical approaches to religious identifications in 3rd-12th century Egyptian papyri through exploration of a variety of case studies in different languages. Of interest to students and scholars of Late Antiquity, Egypt, and Late Antique religion.